1995
DOI: 10.1002/pssb.2221910210
|View full text |Cite
|
Sign up to set email alerts
|

Study of Excitonic Molecules in Monoclinic Zinc Diphosphide Crystals

Abstract: I. S. GORBAN et al. The photoluminescence (PL) spectra of the monoclinic modification of the semiconductor crystal ZnP, (P-ZnP,) are studied under high, intermediate, and low laser excitation intensities at liquid helium temperature. Under high excitation intensities the inverse hydrogenlike M-series was observed. It is symmetrical with the hydrogen-like excitonic series. This M-series is due to the two-electron transitions from the excitonic molecule (biexciton) state to the ground, excited, and ionized excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…(Note that the ordinate is ÀDR.) In b-ZnP 2 the luminescence from an excitonic molecule, namely a biexciton, appears at 1.550 eV [5,8,9]. Therefore, the structure is reasonably attributed to this biexciton transition.…”
Section: Resultsmentioning
confidence: 82%
“…(Note that the ordinate is ÀDR.) In b-ZnP 2 the luminescence from an excitonic molecule, namely a biexciton, appears at 1.550 eV [5,8,9]. Therefore, the structure is reasonably attributed to this biexciton transition.…”
Section: Resultsmentioning
confidence: 82%
“…At high irradiation (in both steady-state and pulse one) authors observed a new narrow line, which was explained as emission from the biexciton liquid state. According to the estimations fulfilled by Gorban et al (1995) authors observed the condensation of the biexcitons due to biexciton-biexciton interaction. It is not Bose-Einstein condensation of particles with wave vectors k ¼ 0.…”
Section: Introductionmentioning
confidence: 82%
“…But there is an active discussion of these results with another explanation (O'Hara and Wolfe, 2000) due to Auger decay process, spatial distribution of exciton gas. *E-mail: sugakov@kinr.kiev.ua Condensed exciton phase was observed in -ZnP 2 crystals (Gorban et al, 1995(Gorban et al, , 1996. In this crystal there is a strong exciton-exciton interaction that causes the biexciton molecule creation with the inordinately high value of the biexciton binding energy (14.9 meV).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Emission B-line is due to the radiative transitions from the ground state of forbidden S-orthoexciton and corresponds to B 1 -line of absorption B-series. Serial laws of excitons in ZnP ЕМs manifest themselves in PL spectra due to twoelectron and two-photon radiative transitions from the ground state of a molecule [9][10][11]. Two-electron transitions occur from the ground state of biexciton to states of excitons of C and A-series (further C and Aexcitons correspondingly).…”
mentioning
confidence: 99%